Features of the development of Galega orientalis Lam. in the conditions of the middle taiga of Western Siberia ... - Moiseeva, Ekaterina A.; Shepeleva, Ludmila F.; Bordey, Rimma Kh. (Altai State University, 2024)
This paper presents the results of an introductory assessment of the Galega orientalis Lam. culture (Eastern Galega) to introduce it as a food crop in extreme Northern environmental conditions. To reach the study aim, we conducted a small plot experiment based on the methodology of B. A. Dospekhov with randomized repetitions. We sowed the eastern Galega uninoculated seeds (the control experiment) in sandy podzolic soil; the seeds inoculated with microbiological fertilizer; binary sowing with legumes (pea). We observed the experiment and accounted for the research parameters in agreement with the standard research methods. The results of this study demonstrate ontogenetic and seasonal development characteristics of the species under review growing in the vicinity of Surgut, its biologic productivity, and the advantages of its use as a feeding crop. We analyzed the efficiency of the inoculation of the seeds with microbiological fertilizer Baikal-EM1 and binary sowing. These measures aimed to enhance the ...